Gua Jepang di Perbukitan Pengklik: Studi Battlefield Archaeology tentang Reverse Slope Defence - Wibisono, Rizky Ramadhani Satrio; Nabila, Aurrelia Kanza (Department of Archaeology, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
The need to understand the military significance and strategic use of the Japanese cave in the Pengklik Hills during World War II, particularly its defensive role and its integration with the surrounding terrain, triggered this research. The Japanese Empire's brief occupation of the Dutch East Indies urged the rapid construction of numerous defensive structures, notably in Yogyakarta. Among these, the Japanese cave in the Pengklik Hills held critical strategic significance within the Imperial Japanese Army's eastern defense network. Through battlefield archaeology, supported by surveys and historical map analysis in QGIS, this research reveals the site's military utility and its reflection of the terrain's geomorphological advantages. The Japanese implemented a reverse-slope defense strategy to safeguard isolated logistics warehouses nestled in the denudational hills. Moreover, the cave served as a pivotal monitoring post, both overseeing regional activities and securing vital communication and transportation routes within Yogyakarta's eastern region. This strategic integration of natural landscape features with military planning highlights the site's essential role in Japan's broader World War II defensive efforts. Hence, this research the importance of understanding the Japanese cave in the Pengklik Hills for enhancing knowledge of WWII military strategies, emphasizing the role of battlefield archaeology in recognizing the intersection of natural landscapes and military tactics, which can inform modern defense planning. === Pentingnya untuk memahami signifikansi militer dan penggunaan strategis gua Jepang di Bukit Pengklik selama Perang Dunia II, khususnya peran defensifnya dan integrasinya dengan medan sekitarnya, memicu penelitian ini. Pendudukan singkat Kekaisaran Jepang di Hindia Belanda mendorong pembangunan cepat berbagai struktur pertahanan, terutama di Yogyakarta. Di antara struktur-struktur tersebut, gua Jepang di Bukit Pengklik memiliki signifikansi strategis yang sangat penting dalam jaringan pertahanan timur Tentara Kekaisaran Jepang. Melalui arkeologi medan perang, yang didukung oleh survei dan analisis peta historis di QGIS, penelitian ini mengungkapkan kegunaan militer situs tersebut dan refleksinya terhadap keunggulan geomorfologi medan. Jepang menerapkan strategi pertahanan lereng terbalik untuk melindungi gudang logistik terisolasi yang terletak di perbukitan yang gundul. Selain itu, gua tersebut berfungsi sebagai pos pemantauan penting, baik untuk mengawasi aktivitas regional maupun mengamankan jalur komunikasi dan transportasi vital di wilayah timur Yogyakarta. Integrasi strategis fitur lanskap alam dengan perencanaan militer ini menyoroti peran penting situs tersebut dalam upaya pertahanan Jepang yang lebih luas selama Perang Dunia II. Oleh karena itu, penelitian ini menyoroti pentingnya memahami gua Jepang di Bukit Pengklik untuk meningkatkan pengetahuan tentang strategi militer Perang Dunia II, menekankan peran arkeologi medan perang dalam mengenali keterkaitan antara lanskap alam dan taktik militer, yang dapat memberikan informasi bagi perencanaan pertahanan modern.